EFEKTIVITAS MASSAGE EFFLEURAGE DAN TERAPI MUSIK TERHADAP PENURUNAN TEKANAN DARAH PADA IBU BERSALIN DENGAN PRE EKLAMSI - Lestari Puji Astuti; Zuliah Zuliah; Tri Ismu Pujiyanto (Universitas Muhammadiyah Kudus, 2020)
ABSTRACTBackground: According to the Indonesian Health Demographic Survey (IDHS) in 2017, the direct cause of the maternal mortality rate (MMR) of 30% was preeclampsia. Preeclampsia can be treated pharmacologically and non pharmacologically. Non-pharmacological treatment is a natural treatment including effluerage massage and music therapy.Objective: To identify and analyze differences in blood pressure reduction in pre-eclampsia mothers before and after massage effleurage and music therapy in the Kragan II Puskesmas maternity room.Methods: The study design used the Two Group Post Test With Control Design. Sampling by accidental sampling. Sampling in this study were 40 women with preeclampsia. Test results using the Mann-Whitney test.Results: With effluarge massage the average blood pressure value was 22.0 while in music therapy 19.00 and obtained ρ was 0.002 (0.05). So Ho refused Ha accepted, which means there are differences in the effectiveness of massage effleurage and music therapy to reduce blood pressure in mothers giving birth with pre-eclampsia in health center II.Conclusion: Massage effleurage is more effective when compared to music therapy in reducing maternal blood pressure. It is expected that health workers to implement an effleurage massage program in women with preeclampsia. Keywords: Massage effleurage, Music Therapy, Preeclampsia